DEVELOPMENT OF SINLEK RICE MILK YOGURT AND SURVIVAL OF LACTIC ACID BACTERIA IN YOGURT - Buppan, Pattakorn; Kosuwin, Rattiporn; Chaihong, Yathip; Supmangsang, Noppawan; Amparam, Sukitta (Srinakharinwirot University Journal of Sciences and Technology, 2021)
The research aimed at the production of Sinlek rice milk yogurt by varying 3 sweeteners (honey, sucrose and fructose). The inoculum (from commercial yoghurt) and Sinlek rice milk mixtures were incubated at 25ºC for 6 hours. Physical, chemical and microbiological properties in the Sinlek rice milk yogurts were compared to the control (commercial yogurt) incubated under similar conditions. The results showed that the three yogurts were decreased in pH and increased in lactic acid contant, but there were not singnificant different (P > 0.05). The honey formula had the highest viscosity (17,369.86 centipoises) and the highest liquid layer separation at 10.49%. The survival rate of lactic acid bacteria was (5.8×109 CFU/g). The Sinlek rice milk yogurt could be kept at 4°C, with the survival of bacteria within 14 days. Afther that the number of bacteria started to decrease. There were no significant difference (P > 0.05) in the number of bacteria among the fomulas.